Maneje todos los aspectos de su vida - Ruderman, Marian N.; Braddy, Phillip W.; Hannum, Kelly; Kossek, Ellen Ernst (Ideas into action guidebooks., 2013)
Managing the demands of the workplace and the responsibilities of the rest of your life can be tricky, especially when you're a driven leader who wants to succeed. This book will show you how to successfully establish and manage work-life boundaries so that you can be more successful at work and at home.